Anorectal Malformations Associated With Labioscrotal Fold Malformation and Perineal Mass in Pediatric Patients: Over a Decade of Experience - Wang, Kai; Peng, Chunhui; Pang, Wenbo; Wang, Zengmeng; Wu, Dongyang; Zhang, Dan; Siyin, Sarah Tan; Chen, Yajun (Frontiers in Pediatrics, 2021)
Background: The triad of anorectal malformation (ARM), labioscrotal fold malformation, and perineal mass has rarely been reported before. The purpose of this study was to review our experience in these patients, describe their characteristics, and discuss the possible pathogenesis. Methods: Seven pediatric patients diagnosed with ARM associated with both labioscrotal fold malformation and perineal mass were included in this study. Medical records of these patients were retrospectively reviewed, and follow-up was held through telephone contact or outpatient service. Results: Among the seven patients were six females and one male, and the age at surgery was between 5.2 and 12.4 months. The ratio of lateral-type to mid-perineum-type labioscrotal fold malformation was 5:2. The ARM type was all rectoperineal fistula. Operation was excision of the malformation and perineal mass at the same time of anoplasty. The pathology was lipoma (three cases), fibroma (one case), lipofibroma (one case), angiolipoma (one case), and mesenchymal hamartoma (one case). All the seven patients had no wound complication, and during the follow-up period of 7–100 months after surgery, none of the seven patients suffered perineal mass recurrence. Bowel control was satisfactory in the follow-up period. Conclusions: There is a low incidence for the triad of ARM, labioscrotal fold malformation, and perineal mass. The nature of this disease is neoplastic overgrowth of intervening mesenchymal tissue, which impedes the continuity of caudal development into normal labioscrotal fold and affects the extension of urorectal septum, leading to ARM. Prognosis is mainly dependent on the type of ARM.